In the district of the Raj. - Gundevia, Y. D. (New Delhi, 1992)
he book presents a wealth of revealing information that not only describes Nehru and his policies, but also frankly delineates other world figures such as Lord Mountbatten, Stalin, and Krishna Menon.
Keywords: Civil servants India British occupations Biography